Enantioselective Biosynthesis of L-Phenyllactic Acid From Phenylpyruvic Acid In Vitro by L-Lactate Dehydrogenase Coupling With Glucose Dehydrogenase - Zhang, Dong; Zhang, Ting; Lei, Yuqing; Lin, Wenqian; Chen, Xingyi; Wu, Minchen (Frontiers in Bioengineering and Biotechnology, 2022)
As a valuable versatile building block, L-phenyllactic acid (L-PLA) has numerous applications in the fields of agriculture, pharmaceuticals, and biodegradable plastics. However, both normally chemically synthesized and naturally occurring PLA are racemic, and the production titer of L-PLA is not satisfactory. To improve L-PLA production and reduce the high cost of NADH, an in vitro coenzyme regeneration system of NADH was achieved using the glucose dehydrogenase variant LsGDHD255C and introduced into the L-PLA production process. Here an NADH-dependent L-lactate dehydrogenase-encoding variant gene (L-Lcldh1Q88A/I229A) was expressed in Pichia pastoris GS115. The specific activity of L-LcLDH1Q88A/I229A (Pp) was as high as 447.6 U/mg at the optimum temperature and pH of 40°C and 5.0, which was 38.26-fold higher than that of wild-type L-LcLDH1 (Pp). The catalytic efficiency (kcat/Km) of L-LcLDH1Q88A/I229A (Pp) was 94.3 mM−1 s−1, which was 67.4- and 25.5-fold higher than that of L-LcLDH1(Pp) and L-LcLDH1Q88A/I229A (Ec) expressed in Escherichia coli, respectively. Optimum reactions of L-PLA production by dual-enzyme catalysis were at 40°C and pH 5.0 with 10.0 U/ml L-LcLDH1Q88A/I229A (Pp) and 4.0 U/ml LsGDHD255C. Using 0.1 mM NAD+, 400 mM (65.66 g/L) phenylpyruvic acid was completely hydrolyzed by fed-batch process within 6 h, affording L-PLA with 90.0% yield and over 99.9% eep. This work would be a promising technical strategy for the preparation of L-PLA at an industrial scale.